Release of Plasminogen Activator from Isolated Perfused Dog Heart - Matsubara, Fujio; Sueishi, Katsuo; Ishii, Yutaka; Tanaka, Kenzo (Thrombosis and Haemostasis, 1985)
The release and the local activity of plasminogen activator (PA) were studied in isolated perfused dog hearts, without or with intimal injury induced by means of a balloon catheter inserted into the left anterior descending coronary artery (LAD). Thrombin but not DFP-thrombin induced a dose-dependent PA release in doses of 8 to 32 units. ADP 20 or 200 μmol but not ergonovine 20 or 200 μg induced a weak PA release. The local PA activity was much lower in the LAD at 1 or 4 weeks after this injury than in the intact LAD. However, the release of PA from the hearts after intimal injury was similar to findings in the intact hearts.We conclude from this study that thrombin plays an important role in regulating the coagulation-fibrinolysis system in endothelial cells and that changes in the properties of the endothelial cells may lead to initiation and enhancement of atherosclerosis.
Keywords: Plasminogen activators; Coronary perfusion; Thrombin; Intimal injury; Arteriosclerosis